VEGF and Cervical Cancer Stage IB – IIA Response after Chemotherapy with Ifosfamide – Cisplatin - Edianto, Deri (Sumatera Medical Journal, 2019)
The aim of this study is to evaluate response of cervical cancer stage IB – IIA after neoadjuvant chemotherapy based on VEGF expression. The data were collected from 51 patients’ cervical cancer stage IB – IIA parafin blocks who received chemotherapy ifosfamide – cisplatin before radical hysterectomy at General Hospital Adam Malik Medan. VEGF expression was evaluated from cervical biopsy tissue, and response therapy was evaluated based on tumor size clinically. 20 out of 51 samples with clinically complete response, and the rest are partial response. 18 out of 20 samples with clinically complete response have negative or weak VEGF expression, and 31 out of 51 samples patients were partialy response with moderate or strong VEGF expression. 23 cases with tumor size > 4 cm and 23 cases stage IIA expressed VEGF moderately or strong. Cervical cancer with tumor size < 4 cm and cervical cenncer stage IB with less expressed of VEGF have good response with chemotherapy adjuvant ifosfamide – cis platin.Keyword: ifosfamide-cisplatin, cervical cancer, VEGF